The common rule is (x - 1, y + 3) can be used to describe the translation.
Step-by-step explanation:
Step 1:
The point J (-3, -4) becomes [tex]J^{1}[/tex] (-4, -1).
In order to write the rule for translation from J to [tex]J^{1}[/tex], we subtract the x coordinate of J from [tex]J^{1}[/tex] and subtract the y coordinate of J from [tex]J^{1}[/tex].
The x coordinate [tex]= -4-(-3) = -4+3 = -1.[/tex]
The y coordinate [tex]= -1-(-4) = -1+4 = 3.[/tex]
Step 2:
So from the calculations, we get that the x coordinate is subtracted by 1 i.e. [tex]x-1[/tex] and the y coordinate is increased by 3 i.e. [tex]y+3[/tex].
So the common rule is (x - 1, y + 3).